O conceito de justiça na República de Platão - Albuquerque, Anne Rodrigues Calmont Franciss de (2021)
In this dissertation we propose to investigate the concept of justice in a given portion of a classic work of philosophy, Plato’s Republic. Our work has been divided into three chapters that are dialectically related. It is expected to present in the first chapter some fundamental elements that frame the historical and theoretical biographical that will frame the work Republic. In the second chapter, we will proceed to a detailed study of the concept of justice in Book I of the book Republic. Reviewing what justice is there, what concept the author presents, also paying attention to how this idea interacts in the organic totality of the Republic. Finally, in the third chapter, we analyze the concept of justice in Books II-V of the work, concluding then that “doing what is proper” can be an appropriate definition of justice, since it constitutes a single principle, the from which the perfect exemplary instances of justice are generated